(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to highlight the insurance brand and its dimensions represented by (equity, awareness, customer loyalty) and to evaluate their impact on achieving sustainable competitive advantage and its dimensions represented by (quality, innovation, cost, and customer responsiveness). The research problem revolves around the main question: Does the management of the studied company recognize the importance of the brand and its role in achieving sustainable competitive advantage? The research was applied in the National Insurance Company. The study relied on a descriptive analytical approach using a questionnaire as the primary data collection tool from a population of (245) employees of the company. The statistical programs (SPSS V.28) and (SMART PLS V.3.3) were used to calculate (weighted mean, standard deviation, coefficient of variation, Pearson correlation coefficient, simple and multiple linear regression, T-test, adjusted R², F-test, exploratory and confirmatory factor analysis). The research reached several findings, the most prominent of which are: • There is a moderate level of interest from the studied company in the brand. 2.There is a strong positive impact of the brand on achieving sustainable competitive advantage.